2021
DOI: 10.1038/s41598-021-03328-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Carica papaya latex on coating of SPIONs for dye removal and drug delivery

Abstract: Latex, a milky substance found in a variety of plants which is a natural source of biologically active compounds. In this study, Latex was collected from raw Carica papaya and was characterized using UV–Vis, FTIR and GC–MS analyses. Super Paramagnetic Iron Oxide Nanoparticles (SPIONs) were synthesized, coated with C. papaya latex (PL-Sp) and characterized using UV–Vis, FT-IR, SEM–EDX, XRD, VSM and Zeta potential analyses. SPIONs and latex coated SPIONs (PL-Sp) were used in batch adsorption study for effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The analyzed sample showed patterns that can be referred to as Fe S1, ESI †) and with results of recent studies. 53,54 There was no superlattice diffraction observed at 210, 213 and 300, indicating the absence of a maghemite phase. It can be concluded that no phase change occurs due to the functionalization of Fe 3 O 4 by MHC3.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The analyzed sample showed patterns that can be referred to as Fe S1, ESI †) and with results of recent studies. 53,54 There was no superlattice diffraction observed at 210, 213 and 300, indicating the absence of a maghemite phase. It can be concluded that no phase change occurs due to the functionalization of Fe 3 O 4 by MHC3.…”
Section: Resultsmentioning
confidence: 98%
“…The characteristic peaks of MHC3@Fe 3 O 4 at 12.6 (111), 30.13° (220), 35.536° (311), 43.17° (400), 57.07° (511), 62.75° (440) correlate with the standard pattern of Fe 3 O 4 , indexed in the ICDD (PDF-2/Release 2011 RDB) DB card number 01-075-0449 for the magnetite phase (Table S1, ESI†) and with results of recent studies. 53,54 There was no superlattice diffraction observed at 210, 213 and 300, indicating the absence of a maghemite phase. It can be concluded that no phase change occurs due to the functionalization of Fe 3 O 4 by MHC3.…”
Section: Resultsmentioning
confidence: 98%
“…S12 †). It was found that for low R-values, a specific polystyrene absorbance band between 220 nm and 230 nm could be observed, 52,53 whereas, at high R-values, no distinct absorbance peak was detected, indicating the dominant presence of iron oxide in the sample. 54 In particular, the optical observations for R-values of 1.25 and 2.5 align with the results obtained from MPS measurements.…”
Section: Monitoring the Effect Of Nanoparticle Concentration On Agglo...mentioning
confidence: 98%
“…The nanoconjugation of curcumin were synthesized by sonicating the latex coated SPIONs with aqua, to that the curcumin mixed with methanol was added by continuous sonication and then it is centrifuged to collect the nanoconjugates. The study showed that Bacillus subtilis and Pseudomonas aeruginosa with SPIONconjugated curcumin had an antibacterial activity than Superparamagnetic Iron Oxide Nanoparticles (SPIONs) alone [44].…”
Section: Curcumin Nanoconjugatementioning
confidence: 99%